PERAN POKDARWIS (KELOMPOK SADAR WISATA) DALAM PENGEMBANGAN DESA WISATA DI DESA PACCEKKE KECAMATAN SOPPENG RIAJA KABUPATEN BARRU - Gustia Jasdar; Muhammad Zulfadli (Universitas Negeri Makassar, 2022)
This Study aims to determine: 1)The role of Pokdarwis (Tourism Awareness Group) in the development of a Tourism Village in Paccekke Village, Soppeng Riaja Kanupaten Barru District. 2)To find out the factors that influence Pokdarwis (Tourism Awareness Group) in the development of Tourism Villages in Paccekke Village, Soppeng Riaja District, Barru Regency, the type of research used is descriptive qualitative. The data collection research techniques used are interviews, observation, and documentation. The data collection process carried out by researchers included: data collection, data reduction, data presentation and drawing conclusions. The results of the research show: 1) The role of the Pokdarwis (Tourism Awareness Group) in the development of a Tourism Village in Paccekke Village, Soppeng Riaja District, Kanupaten Barru, namely facilitating role, educational role, representational role, technical role. 2) To find out the factors that influence Pokdarwis (Tourism Awareness Group) in the development of Tourism Villages in Paccekke Village, Soppeng Riaja District, Barru Regerency, namely the driving factors for goverment support and the inhibiting factors for the lack of network access in Paccekke Village.